A stochastic micro-periodic age-based inventory replenishment policy for perishable goods. (October 2018) - Janssen, Larissa; Diabat, Ali; Sauer, Jürgen; Herrmann, Frank
Highlights: We present a new method to reduce wastes in grocery retail. We propose a micro-periodic replenishment policy for quickly perishable goods. We assume fixed and known lifetime, deterministic lead time, and fixed order cycle. We assume mixed issuing policies, age-based stock, imperfect items, and random demand. The proposed approach leads to significant waste reduction at lower distribution cost. Abstract: In this paper, we propose a micro-periodic inventory replenishment policy for quickly perishable goods with fixed and known lifetime of items, deterministic lead time, fixed given order cycle, mixed issuing policies (FIFO and LIFO), age-based stock, imperfect items and target customer service level under random demand. The inventory policy is based on time of day (morning, midday, afternoon or evening). The results of our simulation study show that the proposed micro-periodic inventory policy leads to waste reduction of 66% as well as a partial decrease in cost compared to inventory policy with planning on a daily basis.